Use of quarry rock dust as a fine aggregate in concrete - Wellala, Dammika P.K. (Curtin University, 2017)
This thesis presents a study on the use of fine crushed aggregates as replacement of natural sand in cement mortar and concrete. Material characterisation of three different types of fine crushed aggregates and their effects on the engineering properties of fresh and hardened mortar and concrete specimens were studied. Use of the fine crushed aggregates up to 40% to 60% can be considered feasible for general structures of grade 40 concrete.